2016
DOI: 10.1080/10410236.2016.1242033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Health Beliefs, Media Perceptions, and Communicative Behaviors on Health Behavioral Intention: An Integrated Health Campaign Model on Social Media

Abstract: Social media have recently gained attention as a potential health campaign tool. This study examines this line of expectation concerning the role social media may play in health campaigns by testing an integrated health campaign model that combines insights from research on social media-specific perceptions and communicative behaviors in order to predict health behaviors. Specifically, this study aims to (a) develop a more holistic social media campaign model for predicting health behaviors in the social media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
23

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 49 publications
2
37
0
23
Order By: Relevance
“…Results from two surveys provided correlational associations between receiving information about HPV and HPV vaccination via social media and positive beliefs about the vaccine and desire to search for more information. 53,55 In focus groups with adolescents in North Carolina, they indicated that they would be generally interested in receiving information about HPV and the HPV vaccine via social media, as long as the messages were interesting and credible. 64 College students in Hawaii also indicated in focus groups that they felt that social media (i.e., Facebook) could be a good platform to share accurate and useful information about HPV and the HPV vaccine but that they would not feel comfortable sharing information with their friends until they felt more knowledgeable about the topics and could personalize the message themselves to make it relevant to their friends.…”
Section: Social Media Use For Information and Discussion About Hpv Anmentioning
confidence: 99%
“…Results from two surveys provided correlational associations between receiving information about HPV and HPV vaccination via social media and positive beliefs about the vaccine and desire to search for more information. 53,55 In focus groups with adolescents in North Carolina, they indicated that they would be generally interested in receiving information about HPV and the HPV vaccine via social media, as long as the messages were interesting and credible. 64 College students in Hawaii also indicated in focus groups that they felt that social media (i.e., Facebook) could be a good platform to share accurate and useful information about HPV and the HPV vaccine but that they would not feel comfortable sharing information with their friends until they felt more knowledgeable about the topics and could personalize the message themselves to make it relevant to their friends.…”
Section: Social Media Use For Information and Discussion About Hpv Anmentioning
confidence: 99%
“…In addition, the information provided by the media may also affect people's emotions and subjective norms, and then affect the public's protective behavior. Related empirical studies have manifested this process in different media platforms, including mass media dominated by newspapers [6], magazines [7], radio [8], television [9], and social media platforms such as social networking sites [10], blogs [11] and instant messaging [12]. During a public health crisis, people can search for and access a large amount of information through various channels including traditional media, interpersonal communications, and new media [13].…”
Section: Introductionmentioning
confidence: 99%
“…The CMM and Health's Media Exposure Understanding the factors that influence the development of precautionary behavior as well as the antecedents of developing precautionary behavior (Sato et al, 2019;Yoo et al, 2018), especially from the awareness perspectives (M. Lee et al, 2015;Papagiannaki et al, 2019), have been common objectives in the health communication literature (Shi et al, 2018). To this effect, there are different outlines to study precautionary behaviors in context of media: the information seeking and the information processing by the individuals in question (Greyson & Johnson, 2016 ;Jiang & Street, 2017).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…In a nutshell, these two aspects to studying precautionary behavior provide better understanding about the strengths and weaknesses of media contents that contribute to the development of precautionary behavior, such as advertising (Shen et al, 2015). Thus, evaluating how health communication contents such as advertising and so on enhance the understanding about development of precautionary behavior (Yoo et al, 2018).…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%